Food, Conservation, and Energy Act of 2008: comparison of 2002 and 2008 conservation programs - Hicks, Erin, author; Seidl, Andrew, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2008)
There are fifteen titles in the Food, Conservation, and Energy Act of 2008 (known as the 2008 Farm Bill). Our focus is the conservation title, Title II, which has seven main conservation programs: the Conservation Reserve Program (CRP), the Wetlands Reserve Program (WRP), the Wildlife Habitat Incentives Program (WHIP), the Environmental Quality Incentives Program (EQIP), the Conservation Stewardship Program (CSP), the Farmland Protection Program (FPP), and the Grassland Reserve Program (GRP). All of these programs are continuations of programs from the 2002 Farm Bill or earlier.
December 2008 Agricultural and resource policy report, no. 9
December 2008.
Keywords: Agricultural conservation -- United States; Agriculture and state -- United States; Incentives in conservation of natural resources -- United States; Land use, Rural -- Law and legislation -- United States; Land use, Rural -- United States; Rural development -- Law and legislation -- United States; Contracts, Agricultural -- United States; Natural resources -- Law and legislation -- United States; Agricultural laws and legislation -- United States; Agricultural subsidies -- Law and legislation -- United States